Предмет: Алгебра,
автор: dashas99299
( x - 2 )x = ( x - 4 ) ( x + 1 ) - 7 решите пожалуйста
Ответы
Автор ответа:
0
x²-2x=x²+x-4x-4-7
x²-2x-x²-x+4x+4+7=0
x+4+7=0
x=-7-4
x=-11
ответ:-11
x²-2x-x²-x+4x+4+7=0
x+4+7=0
x=-7-4
x=-11
ответ:-11
Автор ответа:
0
это чере дискриминант ?
Автор ответа:
0
просто обычное линейное уравнение
Автор ответа:
0
( X - 2 ) * X = ( X - 4 ) * ( X + 1 ) - 7
X^2 - 2X = X^2 + X - 4X - 4 - 7
X^2 - X^2 - 3X + 2X - 11 = 0
- X = 11
X = - 11
X^2 - 2X = X^2 + X - 4X - 4 - 7
X^2 - X^2 - 3X + 2X - 11 = 0
- X = 11
X = - 11
Похожие вопросы
Предмет: Биология,
автор: Аноним
Предмет: Химия,
автор: Vlad14211
Предмет: Қазақ тiлi,
автор: Shdjfhd
Предмет: Литература,
автор: Dimka2402
Предмет: География,
автор: адельвина